2012
DOI: 10.1002/jcla.21523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolonged Storage of Seminal Plasma on Levels of Calcium and Magnesium

Abstract: In any elemental study, the most suitable containers are recommended for storage of the semen/seminal plasma samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…38 Similar chronobiological changes in body was known. 43,44 Present study was restricted to one month period. Singh et al 46 reported seasonal changes in semen electrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…38 Similar chronobiological changes in body was known. 43,44 Present study was restricted to one month period. Singh et al 46 reported seasonal changes in semen electrolytes.…”
Section: Discussionmentioning
confidence: 99%